PENGARUH EKONOMI KELUARGA, LINGKUNGAN TEMAN SEBAYA, DAN KESADARAN MASYARAKAT DALAM PENGAMBILAN KEPUTUSAN UNTUK MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI (Studi pada SMK Swasta di Kecamatan Banjarnegara) - Siti Maesaroh (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2020)
ABSTRACT This research was conducted at some private Vocational Schools in Banjarnegara district. The purpose of the study was to examine the influence of family economic income, peer environment, and public awareness in decision making to continue their higher education at collage. At some reasons, students in private Vacational Schools in Banjarnegara basicly need to work for economic reasons, because some parts of region are still classified as families with low economic income. On the other reason students in the region should be more focused and eager to work to help lift their family’s economy, but in this case students also still make the decision to continue their education to collage. The data used in this research were primary data which was obtained through questionnaires. The sampling technique was the probability sampling technique. Data analysis in this research used multiple regression analysis with SPSS 24. In this research indicated that the family economic income affected decision making, peer environment did not affect the decision making, public awareness affects the decision making. Family economic income variables, peer environment, and community awareness simultaneously affected decision making as much as 52.4%, and the remaining 47.6% was influenced by other variables excluded in this study.